BODY IMAGE AND BODY FAT IN ATHLETES OF FOOT ORIENTEERING RACE (Fiep Bulletin - online, 2011)
The manipulation of diet on the basis of dissatisfaction with body image (BI) is observed both among young non-athletes and between athletes. The standard of beauty associated with thinness is one of the factors that contribute to young people try to adjust, often using methods not healthy. Objective: This study aimed to verify the relationship between dissatisfaction with the BI and body fat (BF) in athletes of Foot Orienteering Race. Materials and Methods: Nine athletes were evaluated (21 ± 4.9 years). Body composition was obtained by anthropometric method (International Society for Advancement in Kinanthropometry – ISAK), and satisfaction with body image with the Body Shape Questionnaire - BITE. The statistical analysis was performed in Excel 2000, Microsoft. Results Discussion: The athletes have satisfactory BF suitable for age and gender. The correlation coefficient between BI and BF was p=0.38, not statistically significant, indicates any relationship between the variables considered. Despite the high percentage of athletes are dissatisfied with the BI, there is the presence of athletes with changes in BSQ (33%). Conclusions: The results indicate no relationship between BF and BI, and the presence of dissatisfaction with the IC in 33% in the athletes of Foot Orienteering Race.
Keywords: body image; body fat; foot orienteering race